Exploring practical conservation measures for pelagic thresher sharks using local knowledge in Sunda Banda seascape - Shidqi, Rafid A.; Bang, Yodhikson M.; Basrun, Samsul; Sari, Dewi Ratna; Tukan, Maria Bernadeth Y.; Booth, Hollie (Frontiers in Ocean Sustainability, 2025)
The pelagic thresher shark (Alopias pelagicus) is an evolutionarily distinct and globally endangered species, with population declines primarily attributed to targeted fishing and bycatch in both small-scale and industrial fisheries. As the world's largest shark fishing nation, Indonesia is a global priority for pelagic thresher shark conservation. Recent studies have revealed that the Sunda Banda seascape in eastern Indonesia is a hotspot and migration route for this species. While many fisheries operate in this seascape, there is a lack of data regarding the interactions between these fisheries and pelagic thresher sharks in the area, which hinders efforts to mitigate overfishing and promote conservation. This study addresses this gap by utilizing local ecological knowledge from fishers in Banda, Central Maluku, Indonesia. We employed a mixed-methods approach, combining surveys (N = 52) and focus group discussions (N = 25), with fishers selected through purposive and snowball sampling. This methodology enabled us to explore Banda fishers' socio-economic attributes, knowledge, attitudes, and interactions concerning pelagic thresher sharks and their conservation. Our results identified 16 locations where fishers captured or sighted pelagic threshers, all of which overlap with Ay-Rhun and Banda Sea marine protected areas. We found that fishers primarily depended on fishing for their livelihoods, with some having participated in shark fisheries and trade in the past. However, pelagic threshers are not a target species due to their low economic value. Instead, they are accidentally caught in small-scale handlines and purse seine fisheries associated with fish-aggregating devices. The meat is consumed or sold locally as a cheap animal protein, particularly during times of low fish catch. Fishers highlighted the costs associated with pelagic thresher bycatch, such as increased expenses to repair broken nets. This suggests that potential win–win approaches, like incentive-based interventions to encourage bycatch release, can serve as feasible solutions to address this conservation issue.